The Role of Autophagy in Nanoparticles-Induced Toxicity and Its Related Cellular and Molecular Mechanisms - Li, Yubin; Ju, Dianwen (Advances in experimental medicine and biology, 2018)
In the past decades, nanoparticles have been widely used in industry and pharmaceutical fields for drug delivery, anti-pathogen, and diagnostic imaging purposes because of their unique physicochemical characteristics such as special ultrastructure, dispersity, and effective cellular uptake properties. But the nanotoxicity has been raised over the extensive applications of nanoparticles. Researchers have elucidated series of mechanisms in nanoparticles-induced toxicity, including apoptosis, necrosis, oxidative stress, and autophagy. Among upon mechanisms, autophagy was recently recognized as an important cell death style in various nanoparticles-induced toxicity, but the role of autophagy and its related cellular and molecular mechanisms during nanoparticles-triggered toxicity were still confusing. In the chapter, we briefly introduced the general process of autophagy, summarized the different roles of autophagy in various nanoparticle-treated different in vitro/in vivo models, and deeply analyzed the physicochemical and biochemical (cellular and molecular) mechanisms of autophagy during nanoparticles-induced toxicity through listing and summarizing representative examples. Physicochemical mechanisms mainly include dispersity, size, charge, and surface chemistry; cellular mechanisms primarily focus on lysosome impairment, mitochondria dysfunction, mitophagy, endoplasmic reticulum stress and endoplasmic reticulum autophagy; while molecular mechanisms were mainly including autophagy related signaling pathways, hypoxia-inducible factor, and oxidative stress. This chapter highlighted the important role of autophagy as a critical mechanism in nanoparticles-induced toxicity, and the physicochemical and biochemical mechanisms of autophagy triggered by nanoparticles might be useful for establishing a guideline for the evaluation of nanotoxicology, designing and developing new biosafety nanoparticles in the future.